Osobnost vedoucího manažera v sociální sféře - Pitnerová, Dagmar (Univerzita Pardubice, 2008)
Benefit is focused on personality of manager in social sphere. In describes his expert knowledges, way o human resource management, motivation, planning, control and emphasizes teamwork too. It presents research which was realised by specialists in social services during 2006- 2007.
Keywords: manager; style direction; planning; motivation; team work